Territorial cohesion and democracy in the EU - Kölling, Mario (Política y Sociedad, 2021)
Inequality not only has an economic and social dimension, but also a territorial dimension with relevant political implications. The clear regional differences in economic development and employment and therefore in quality of life and opportunities in the European Union (EU) make the social situation increasingly unequal in territorial terms. There seems to be a growing consensus that large and dynamic urban areas are the future, while rural areas are perceived as having low potential. In many EU Member States, populism as a political force seems to grow in these so-called "places that don’t matter", in numbers which may create systemic risks. The strengthening of the economic, social and territorial cohesion is one of the Union’s main objectives. Already the Treaty of Rome (1957) established mechanisms to foster the economic and social cohesion, but it was not until the Treaty of Lisbon that a third dimension, the territorial cohesion, was introduced. Taking advantage of the tenth anniversary of the entry into force of the Lisbon Treaty, the aim of this text is to analyse the concept and instruments of EU’s territorial cohesion policy in order to study the challenges of this policy.